2021
DOI: 10.3389/fncel.2021.765541
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of α9α10 Nicotinic Receptors With Peptides and Proteins From Animal Venoms

Abstract: Unlike most neuronal nicotinic acetylcholine receptor (nAChR) subunits, α7, α9, and α10 subunits are able to form functional homo- or heteromeric receptors without any β subunits. While the α7 subtype is widely distributed in the mammalian brain and several peripheral tissues, α9 and α9α10 nAChRs are mainly found in the cochlea and immune cells. α-Conotoxins that specifically block the α9α10 receptor showed anti-nociceptive and anti-hyperalgesic effects in animal models. Hence, this subtype is considered a dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…α9α10 nAChR has been proven to be expressed in immune cells and mediate noncanonical metabotropic pathways that regulate the expression of pro-inflammatory cytokine IL-β [31]. Tsetlin et al reported that α9α10 nAChR antagonists enhanced the expression of the anti-inflammatory cytokine IL-10 on mouse bone marrow granulocytes upon LPS stimulation [32]. AlSharari et al reported that the α9α10 nAChR antagonist RgIA was effective in an experimental colitis mice model and reduced the increased level of TNF-α, suggesting α9α10 nAChR as a potential target for inflammatory disorders [33].…”
Section: Discussionmentioning
confidence: 99%
“…α9α10 nAChR has been proven to be expressed in immune cells and mediate noncanonical metabotropic pathways that regulate the expression of pro-inflammatory cytokine IL-β [31]. Tsetlin et al reported that α9α10 nAChR antagonists enhanced the expression of the anti-inflammatory cytokine IL-10 on mouse bone marrow granulocytes upon LPS stimulation [32]. AlSharari et al reported that the α9α10 nAChR antagonist RgIA was effective in an experimental colitis mice model and reduced the increased level of TNF-α, suggesting α9α10 nAChR as a potential target for inflammatory disorders [33].…”
Section: Discussionmentioning
confidence: 99%
“…RgIA4 directly and positively modulated the release of the pro-inflammatory cytokine, IL-1β, in a monocytic cell line [ 31 ]. In contrast, RgIA also increased cellular release of the potent anti-inflammatory cytokine, IL-10, from isolated granulocytes, increased their cell adhesiveness, and reduced reactive oxygen species in these cells [ 52 ]. Despite opposing effects in different cell types, the net in vivo effects of RgIA and RgIA4 are anti-inflammatory and analgesic, providing long-lasting relief and neuronal protection.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity block of rα9α10 nAChRs by RgIA has been attributed, in part, to residues Asp5, Pro6; Arg7 in loop I and Arg9 in loop II [31]. The α9α10 nAChR subtype, which is critical for mediating synaptic transmission from the medial olivocochlear to the cochlear hair cells, has also been implicated in a series of pathological conditions, including neuropathic pain [26,[32][33][34][35][36], tumor proliferation [37][38][39], and immune-mediated disorders [40][41][42][43][44]. Considering the high affinity of RgIA towards this receptor subtype [11,45], its discovery led to the possibility of studying the role of α9α10 nAChRs in several diseases.…”
Section: Rgiamentioning
confidence: 99%
“…RgIA4 (see below for its amino acid composition), a RgIA derivative that lacks GABA B R activity, maintains the capacity to prevent the development of neuropathic pain [36,65,66]. Moreover, RgIA, which induces calcium transients in murine granulocytes, decreased reactive oxygen species production [42,44] and increased the production of the anti-inflammatory interleukin-10 in these cells. Even in this case, the α9α10 nAChR mechanism is more suitable than the GABA B R mechanism for explaining such regulation, given that the inhibition of VGCC currents mediated by GABA B R might result in lowering intracellular calcium, not in its increase [42].…”
Section: Analgesic and Disease-modifying Effects Of Rgiamentioning
confidence: 99%